ANALISIS PENGARUH PERSENTASE KEPEMILIKAN ASING, LATAR BELAKANG PENDIDIKAN KOMITE AUDIT, UKURAN KAP, UMUR PERUSAHAAN, PROFITABILITAS, DAN SOLVABILITAS TERHADAP AUDIT DELAY - Vega Lienardi; Theresia Dian Widyastuti (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
The purpose of this research is to analyze the effect of foreign ownership percentage, audit committee education background, size of public accounting firm, company age, profitability and solvency to audit delay in mining companies that listed in Indonesia Stock Exchange (IDX). This study takes company samples in 2011 - 2015. This research uses data from the Fact Book and the company's financial statements. The total sample in this research are 80 companies during 2011 - 2015. The significance value used in this research is 5%. Multiple linear regression testing was performed using version 17.00 SPSS program. The result of the research shows that (1) the foreign ownership percentage has no effect on audit delay (2) the audit committee education background has no effect on audit delay (3) size of public accounting firm has a significant negative effect on audit delay (4) firm's age has a significant negative effect on audit delay (5) profitability has a significant negative effect on audit delay, and (6) solvency has no effect on audit delay.